Acute intensive insulin therapy exacerbates diabetic blood-retinal barrier breakdown via hypoxia-inducible factor-1α and VEGF - Poulaki, Vassiliki (American Society for Clinical Investigation, 2002)
Acute intensive insulin therapy is an independent risk factor for diabetic retinopathy. Here we demonstrate that acute intensive insulin therapy markedly increases VEGF mRNA and protein levels in the retinae of diabetic rats. Retinal nuclear extracts from insulin-treated rats contain higher hypoxia-inducible factor-1α (HIF-1α) levels and demonstrate increased HIF-1α–dependent binding to hypoxia-responsive elements in the VEGF promoter. Blood-retinal barrier breakdown is markedly increased with acute intensive insulin therapy but can be reversed by treating animals with a fusion protein containing a soluble form of the VEGF receptor Flt; a control fusion protein has no such protective effect. The insulin-induced retinal HIF-1α and VEGF increases and the related blood-retinal barrier breakdown are suppressed by inhibitors of p38 mitogen-activated protein kinase (MAPK) and phosphatidylinositol (PI) 3-kinase, but not inhibitors of p42/p44 MAPK or protein kinase C. Taken together, these findings indicate that acute intensive insulin therapy produces a transient worsening of diabetic blood-retinal barrier breakdown via an HIF-1α–mediated increase in retinal VEGF expression. Insulin-induced VEGF expression requires p38 MAPK and PI 3-kinase, whereas hyperglycemia-induced VEGF expression is HIF-1α–independent and requires PKC and p42/p44 MAPK. To our knowledge, these data are the first to identify a specific mechanism for the transient worsening of diabetic retinopathy, specifically blood-retinal barrier breakdown, that follows the institution of intensive insulin therapy.